OSIALISASI DAN PELATIHAN PENYUSUNAN LAPORAN KEUANGAN UMKM KERAJINAN SONGKET MAYANG PALEMBANG - Saggaf, Abdullah; Ichsan Siregar, Muhammad; Hidayat, Muhammad; Sartika Pratiwi, Trie; Efriandy, Iwan (Universitas katolik Musi Charitas, 2020)
Product development for small and medium enterprises is very important. In the era ofglobalization, small and medium enterprises are required to be creative and able to have highinnovation. One business that has the potential for small and medium enterprises in Palembangnow is songket craft. To maintain and increase production by developing products, creatingproduct innovation, managing finances and marketing well. The conditions that occur in SongketMayang have not maximized business planning, do not understand simple financial reports andhave not maximized marketing strategies both manually and informatively in technology. For thisreason, we assisted by providing socialization and training in the preparation of MSME financialreports for Palembang songket craft with the team.